A BCJR-like Labeling Algorithm for Tail-Biting Trellises - Nori, Aditya; Shankar, Priti (Proceedings of the IEEE International Symposium on Information Theory (ISIT), 2003)
WE describe two constructions for tail-biting trellises that are very similar to the well known BCJR construction for conventional trellises. The constructions lead to a simple proof of the fact that there exist linear tail-biting trellises for a linear code and its dual, which have the same state-complexity profiles.